Wide Spread of blaCTX–M–9/mcr-9 IncHI2/ST1 Plasmids and CTX-M-9-Producing Escherichia coli and Enterobacter cloacae in Rescued Wild Animals - Haenni, Marisa; Métayer, Véronique; Jarry, Romane; Drapeau, Antoine; Puech, Marie-Pierre; Madec, Jean-Yves; Keck, Nicolas (Frontiers in Microbiology, 2020)
Wildlife has recently been pinpointed as one of the drivers of dissemination of genes conferring resistances to clinically important antimicrobials. The presence of both extended-spectrum beta-lactamase- (ESBL) and carbapenemase-encoding genes has notably been reported in wild birds, that can act as sentinels of antimicrobial resistance (AMR) contamination but also as long-distance spreaders in case of migratory birds. Here, 424 wild birds brought to a rescue center in France were sampled over a 6-month period. These birds encompassed 62 different sedentary or migratory species. A further 16 wild mammals present in the center were also investigated. No carbapenemase-producer was found, but we identified a surprisingly high proportion (24.1%) of ESBL-positive isolates. A total of 144 non-duplicate isolates were collected, including Escherichia coli (n=88), Enterobacter cloacae (n=51) and Citrobacter freundii (n=5), of which 123 carried the blaCTX-M-9 gene. PFGE, phylogroup and MLST revealed the presence of a limited number of ESBL-positive clones circulating in these animals, all presenting multiple associated resistances. Next-generation sequencing on a subset of isolates, followed by Southern blot hybridization, showed the wide dissemination of an IncHI2/ST1 plasmid carrying the blaCTX-M-9, blaSHV-12 and mcr-9 genes. In all, our results undoubtedly reflect cross transmissions of ESC-R Enterobacteriaceae within the rescue center – similarly to nosocomial spreads observed at hospital, rather than the true bacterial flora of birds. We also showed that the spread of ESC-R in this rescue center did not only rely on clonal but also on a highly successful plasmidic transmission. Since most animals are intended to get back to nature after a few days or weeks, this is obviously an issue with regard to ESBL dissemination in natural environments.